Social commerce as a tool of the digital economy: concepts and characteristics - Svitlana Kulakova (Фінансово-кредитні системи: перспективи розвитку.)
To succeed in today’s world, modern businesses need an online presence due to the growth of e-commerce, which involves selling goods and services online. E-commerce is not just expanding; it is also transforming the direction of business development. Now, companies must operate in a digital environment, create social platforms, influence consumers, and maintain their interest. This is why the new trend in electronic business and marketing is called ‘social commerce. Social commerce represents an innovative branch of e-commerce that emerged from the active integration and use of popular social networks. It enables consumers to interact on online platforms, unlocking new opportunities for buying and selling goods and services directly within these networks. Recent advancements in information technology, particularly with the advent of Web 2.0 technologies, alongside the widespread adoption of social networks and related services, have facilitated the creation and active development of new social platforms. These platforms significantly enhance the effectiveness of social commerce by expanding opportunities for users to make purchases, share reviews, and exchange recommendations in an interactive environment that suits their needs. Summarizing the ideas presented in the article, several key conclusions highlight the complex and multifaceted nature of social commerce. It combines social interactions with commercial activities, regarded by the scientific community as a multi-component and complex phenomenon. Social commerce encompasses various aspects, including modern technologies, the impact of social environments, diverse marketing strategies, consumer behavior patterns, and processes focused on creating and enhancing value for consumers. To gain a deep understanding of social commerce, it is essential to comprehensively analyze all these approaches, as each contributes uniquely to the overall structure of this phenomenon, helping to form a complete picture of its nature. Only a holistic approach can reveal the full scope and complexity of social commerce.